Optimization of nanoemulsified systems containing lamellar phases for co-delivery of celecoxib and endoxifen to the skin aiming for breast cancer chemoprevention and treatment - Mojeiko, Gabriela; Apolinário, Alexsandra Conceição; Salata, Giovanna Cassone; Chorilli, Marlus [UNESP]; Lopes, Luciana B. (Elsevier, 2022)
We proposed an innovative nanoemulsified system containing lamellar phases (NLP) produced by a low-energy method to enable the local-transdermal co-delivery of celecoxib and endoxifen as a potential strategy for breast cancer local chemoprevention. The NLPs were composed of surfactant:oil phase at 1:1 (w/w) and 80% water. Oleic or caprylic acid was added (2% or 5% w/w) as penetration enhancer. NLP droplet size was influenced by the type and concentration of the penetration enhancer, ranging from 290 to 450 nm with negative zeta potential. They presented pseudoplastic behavior, and after drug addition, elastic and bioadhesive properties were displayed. Compared to water (control), all formulations increased transepidermal water loss by 8.5–12.9 times, with the NLP containing 5% oleic acid promoting a more pronounced effect. No signs of vascular toxicity were observed in the HET-CAM model, suggesting safety. All NLPs increased the penetration of celecoxib and endoxifen in the skin, but the formulation containing 5% oleic acid was more effective, promoting ~ 3–22-fold increases in cutaneous delivery and ~ 11–20-fold increases in transdermal drug delivery. Combination of celecoxib and endoxifen in this NE reduced the viability of cancer cells in a synergistic manner compared to the use of isolated drugs. These results suggest the potential applicability of the NE for topical delivery and breast cancer chemoprevention.
Keywords: Caprylic acid; Celecoxib; Chemoprevention; Co-delivery; Endoxifen; Local-transdermal therapy; Oleic acid